2021
DOI: 10.1186/s12905-021-01384-4
|View full text |Cite
|
Sign up to set email alerts
|

Different clinical parameters inform epicardial fat thickness in pre- and post-menopausal women with obstructive sleep apnea

Abstract: Background Obstructive sleep apnea (OSA) is a sleep-related disorder with breathing difficulties. Previous studies revealed that epicardial fat thickness (EFT) correlates with OSA severity. Interestingly, female patients display a stronger EFT-OSA correlation than males. The purpose of this study is to investigate the relationship between EFT and different clinical characteristics in pre- and post-menopausal women diagnosed with OSA. Methods Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…We observed that the mean epicardial fat thickness of OSA patients was significantly higher compared to the control group. These results are consistent with the study of Zhang et al, who demonstrated that EFT was positively correlated with OSA [56]. More recently, a meta-analysis study demonstrated that patients with OSA had higher EFT levels compared to patients without OSA, as measured by echocardiography.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that the mean epicardial fat thickness of OSA patients was significantly higher compared to the control group. These results are consistent with the study of Zhang et al, who demonstrated that EFT was positively correlated with OSA [56]. More recently, a meta-analysis study demonstrated that patients with OSA had higher EFT levels compared to patients without OSA, as measured by echocardiography.…”
Section: Discussionsupporting
confidence: 92%